Inspirational hospitality entrepreneurship model in cultivating the entrepreneurship education among Malaysian higher institutions hospitality students / Wan Nor Bayah Wan Kamarudin ... [et al.] - Wan Kamarudin, Wan Nor Bayah; Mohd Fuza, Zatul Iffah; Mat Ghani, Amanina; Wan Nawawi, Wan Nazriah; Hamid, Rasidah; Mohd Daud, Norzaidi (Universiti Teknologi MARA, 2023)
The Graduates Statistics 2020 data from the Department of Statistics Malaysia (DOSM) reported a 4.4 per cent increase of graduates from 5.13 million in 2019 to 5.36 million students in 2020. However, in the same year, the Ministry of Higher Education revealed that the marketability of Malaysian graduates had declined from 86.2 per cent in 2019 to 84.4 per cent in 2020, due to the Covid-19 pandemic. Aligned with the issues, the Malaysian Ministry of Higher Education has endorsed entrepreneurship education in all higher education institutions as an initiative to encourage students to enrol in entrepreneurship courses and activities. This prompted the current study, which sought to determine the relationship between psychological capital (PsyCap), higher education institutions (HEIs), and entrepreneurial intention (EI) among Malaysian hospitality students. In the first phase of the current study, a quantitative study employing the sequential explanatory mixed method design was conducted via an online survey at five (5) public HEIs in Malaysia, yielding a total sample size of 297 participants. Partial Least Squares-Structural Equation Modelling (PLS-SEM) software was used to analyse the study’s data structuring obtained via probability sampling. Semistructured interviews were also conducted in the second phase of the current study to get in-depth view of the relevant skills of successful entrepreneurs. The data were analyses using NVIVO 12. The study has successfully purposed a model for entrepreneurship education, the Inspirational Hospitality Entrepreneurship Model (IHEM), which highlights the eight relevant skills to being a successful hospitality entrepreneur. Overall, the current study discovers that PsyCap has an impact on students' attitudes towards entrepreneurship. This study perhaps could benefits to stakeholders, specifically those in higher institutions, by validating the emerging need for hospitality students to be equipped with high spirit, high creativity, and a wealth of new ideas to produce more young hospitality entrepreneurs for Malaysia to be resilient in the future.